Using relative-speed-of-processing to explain the shielding function of task rules. Issue 11 (November 2022) - Huang, Liang; Li, Bingxin; Yan, Panjie; Xu, Chen; Tian, Xueyin; Han, Chengyang; Li, Xiangqian
In choice reaction tests, applying task rules instead of responding associatively can help participants shield against interference from distractors. However, the mechanism of such shielding functions remains unclear. Through four experiments, we show how the shielding function can be explained by the relative-speed-of-processing theory. Experiment 1A demonstrated that applying task rules can reduce the relative processing advantage of the distractor by facilitating the target processing speed, thereby eliminating the interference effect. In Experiment 1B and 1C, we manipulated the relative processing advantage between targets and distractors by adjusting the temporal sequence of the presence of the targets and distractors: stimuli appearing first would gain more relative processing advantage. The results showed that when the relative processing advantage of a distractor was large enough, applying task rules cannot help participants shield against the interference. Contrarily, when the relative processing advantage of the distractor was small, even without applying task rules, participants did not experience the interference. In Experiment 2, we directly manipulated the processing speed of the targets and the distractor, so that participants who responded associatively would facilitate target processing speed, but participants who applied task rules would not. Contrary to previous studies but in line with our prediction, in Experiment 2, only participants who applied task rules had interference effects. Our results suggested that applying the task rule might not help shield against the interference directly. Instead, applying task rules improves target processing speed, which in turn reduces the relative processing advantage of the distractor and eliminates the interference.